2020
DOI: 10.3758/s13423-020-01850-4
|View full text |Cite
|
Sign up to set email alerts
|

Taking the perspectives of many people: Humanization matters

Abstract: In a busy space, people encounter many other people with different viewpoints, but classic studies of perspective-taking examine only one agent at a time. This paper explores the issue of selectivity in visual perspective-taking (VPT) when different people are available to interact with. We consider the hypothesis that humanization impacts on VPT in four studies using virtual reality methods. Experiments 1 and 2 use the director task to show that for more humanized agents (an in-group member or a virtual human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…It has been proposed that mentalizing abilities can be influenced by the ability to detect others’ gaze direction ( Stephenson et al., 2021 ), and that we may have an advantage in taking the perspective of agents we perceive similar to ourselves (e.g., ingroup vs outgroup; Ye et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that mentalizing abilities can be influenced by the ability to detect others’ gaze direction ( Stephenson et al., 2021 ), and that we may have an advantage in taking the perspective of agents we perceive similar to ourselves (e.g., ingroup vs outgroup; Ye et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absolute differences in response times between avatars were minimal and the effects of social cues, compared to spatial cues like angle, were small. Previous research that has found larger group-related effects embedded VSPT in social contexts that explicitly relate to the target agents (Todd et al, 2011;Ye et al, 2020). For example, communicative tasks (Savitsky et al, 2011) indicate a "mind to be known," evoking theory-of-mind, and tasks pre-testing to allocate groups (Ye et al, 2020) suggest avatar similarity and differences are important considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research that has found larger group-related effects embedded VSPT in social contexts that explicitly relate to the target agents (Todd et al, 2011;Ye et al, 2020). For example, communicative tasks (Savitsky et al, 2011) indicate a "mind to be known," evoking theory-of-mind, and tasks pre-testing to allocate groups (Ye et al, 2020) suggest avatar similarity and differences are important considerations. Furthermore, Tarampi et al (2016) found that framing spatial orientation tasks as measuring empathy instead of spatial skills significantly improved female performance.…”
Section: Discussionmentioning
confidence: 99%
“…Humanisation can also impact VPT through top-down processes, where prior information, context or task instructions make a participant believe the agent is similar to themselves. Recent findings revealed that compared with an outgroup member, we have a stronger propensity to take an ingroup member’s perspective ( Vaes et al, 2004 ; Simpson and Todd, 2017 ; Ye et al, 2021 ). The ingroup effect is not restricted to groups formed by physical features, but also applies to arbitrarily formed groups.…”
Section: Introductionmentioning
confidence: 99%
“…Visual perspective taking (VPT) refers to the ability to consider what another person can see and how they see it ( Flavell, 1977 ; Samson et al, 2010 ; Elekes et al, 2016 ). Previous studies on VPT suggest that people are more likely to take the perspective of an agent that they consider to be human, including agents that move like a human, look like a human, and belong to an in-group ( Vaes et al, 2004 ; Mazzarella et al, 2012 ; Zhao et al, 2016 ; Ye et al, 2021 ; Zhao and Malle, 2022 ). Based on these findings, our previous research proposed the ‘humanisation account’ of VPT, suggesting that the psychological process of humanisation might serve as a gateway towards spontaneous VPT.…”
Section: Introductionmentioning
confidence: 99%